Investigation of English Proficiency in Rural Students at SMK Pariwisata Aiq Bual in The School Year 2025/2026 - Hikmah; Zahratul Fikni; Hajriana Arfah; Laila Wati (Journal of Classroom Action Research, 2025)
Abstract: This study aimed to investigate the level of English proficiency and the factor hat influence of the tenth-grade students from SMK Pariwisata Aiq Bual, located in a rural area. The research used a qualitative approach with classroom observation, interviews, and English tests to collect data on students’ abilities in vocabulary, graThis study employed a qualitative case study approach to investigate the English proficiency profile of tenth-grade students at SMK Pariwisata Aiq Bual, a rural vocational school in Central Lombok. Data were collected through classroom observations, interviews, and English proficiency tests to gain a holistic understanding of students’ abilities in vocabulary, grammar, reading, and speaking. The findings revealed that most students demonstrated average proficiency in vocabulary and grammar, good reading skills, and weaknesses in speaking performance due to limited exposure, low confidence, and minimal opportunities for real communication. The study identified several key factors influencing students’ English proficiency, including psychological aspects (motivation and anxiety), environmental limitations (lack of English exposure and learning resources), and instructional practices that remain grammar-focused rather than communicative. Despite these challenges, students showed high motivation and positive attitudes toward learning English, especially in relation to their future tourism careers. The study recommends implementing communicative and contextualized teaching approaches, increasing authentic language exposure, and enhancing teacher professional development to strengthen students’ overall English proficiency and confidence in using the language in real-life contexts.mmar, reading, and speaking. The results showed that most students fell into the Average category for vocabulary and grammar, while their reading skills were mostly Good. Speaking was the most challenging skill for some students, though their confidence and participation in class were generally high. Students tried to improve their English through practice in and outside the classroom, memorizing vocabulary, and interacting with tourists or native speakers. This study suggests that students are motivated and have a positive attitude toward learning English, but they need structured support to improve vocabulary, grammar, and speaking skills.